Frequent external focus feedback enhances motor learning - Wulf, Gabriele; Chiviacowsky, Suzete; Schiller, Eduardo; Ávila, Luciana T. (Frontiers in Psychology, 2010)
The present study examined the hypothesis that feedback inducing an external focus of attention enhances motor learning if it is provided frequently (i.e., 100%) rather than less frequently. Children (10-12 year olds) practiced a soccer throw-in task and were provided feedback about movement form. The feedback statements, provided either after every (100%) or every third (33%) practice trial, were similar in content but induced either an internal focus (body-movement related) or external focus (movement-effect related). The results demonstrated that learning of the movement form was enhanced by external-focus feedback after every trial (100%) relative to external-focus feedback after every third trial (33%) or internal-focus feedback (100%, 33%), as demonstrated by immediate and delayed transfer tests without feedback. There was no difference between the two internal-focus feedback groups. These findings indicate that the attentional focus induced by feedback is an important factor in determining the effectiveness of different feedback frequencies. We argue that the informational properties of feedback cannot sufficiently account for these and related findings, and suggest that the attentional role of feedback be given greater consideration in future studies.